In Vivo Deletion of CAR Resulted in High Bone Mass Phenotypes in Male Mice. Issue 5 (May 2014) - Cho, Hwa Young; Jung, Ju‐Yeon; Park, Hyojung; Yang, Jae‐Yeon; Jung, Solip; An, Jee Hyun; Cho, Sun Wook; Kim, Sang Wan; Kim, Seong Yeon; Kim, Jung Eun; Park, Young Joo; Shin, Chan Soo
Abstract Constitutive androstane receptor (CAR) was originally identified as xenobiotic sensor that regulates the expression of cytochrome P450 genes. However, recent studies suggest that this nuclear receptor is also involved in the regulation of energy metabolism including glucose and lipid homeostasis. This study investigated the role of CAR in the regulation of bone mass in vivo using CAR−/− mice. Endogenous mRNA expression of CAR was observed in both primary osteoblasts and osteoclast precursors. CAR−/− mice have exhibited significant increase in whole body bone mineral density (BMD) by 9.5% (P < 0.01) and 5.5% (P < 0.05) at 10 and 15 weeks of age, respectively, compared with WT mice in males. Microcomputed tomography analysis of proximal tibia demonstrated a significant increase in trabecular bone volume (62.7%), trabecular number (54.1%) in male CAR−/− mice compared with WT mice. However, primary culture of calvarial cells exhibited no significant changes in osteogenic differentiation potential between CAR−/− and WT. In addition, the number of tartrate‐resistant acid‐phosphatase positive osteoclasts in the femur and serum level of CTx was not different between CAR−/− and WT mice. The higher BMD and microstructural parameters were not observed in female mice. Interestingly, serum level of testosterone in male CAR−/− mice was 2.5‐fold higher compared with WT mice and the mRNA expressions of Cyp2b9 and 2b10 in the liver, which regulate testosterone metabolism, were significantly down‐regulated in male CAR−/− mice. Furthermore, the difference in BMD between CAR−/− and WT mice disappeared at 8 weeks after performing orchiectomy. CAR−/− mice also exhibited significant increase in serum 1, 25(OH)2D3 levels but Cyp 27B1 which converts 25(OH)D3 to 1, 25(OH)2D3 was significantly down‐regulated compared to WT mice. These results suggest that in vivo deletion of CAR resulted in higher bone mass, which appears to be a result from reduced metabolism of testosterone due to down‐regulation of Cyp2b. J. Cell. Physiol. 229: 561–571, 2014. © 2013 Wiley Periodicals, Inc.